PSYCHOMETRIC PROPERTIES OF THE SHORT VERSION OF GENERIC CONSPIRACIST BELIEFS SCALE (GCB-15) TRANSLATED IN MACEDONIAN LANGUAGE (Annual of the Faculty of Philosophy in Skopje, 2024)
This research evaluates the psychometric characteristics of the short versionof Generic Conspiracist Beliefs scale (GCB-15) translated in Macedonian language.A convenient online sample of 615 ethnic Macedonians (53.2% women, average ageM=30.6; SD=20.4) from 18 cities participated voluntarily in the data gathering process.The translation process involved two independent interpretations, a back-translation,and consensus discussions.The mean scores for GCB-15 subscales were higher compared to other studies,possibly indicating elevated conspiracist beliefs in this population. The results fromthe exploratory factor analysis suggested a two-factor structure, distinguishing generalconspiracist ideation and extraterrestrial beliefs. The confirmatory factor analysissupported this model over one- or five-factor structures. The Cronbach Alpha indicesindicated acceptable internal consistency of all subscales (from α=.61 to α=.80) and veryhigh one for the overall scale (α=.91). Convergent validity was confirmed by examiningcorrelations with conspiracist mentality and populist attitudes, while discriminant validitywas demonstrated by non-association with emotional intelligence. Criterion-basedvalidity was confirmed by predicting belief in COVID-19 conspiracy theory, whereasknown groups’ validity showed differences in GCB based on education, economic status,and life satisfaction, however, the hypotheses were supported only partially. In conclusion,the GCB-15 translated in Macedonian proves to be a valuable instrument forstudying conspiracist beliefs in this cultural context, offering additional support for itseffectiveness across various cultures.
Keywords: generic conspiracist beliefs; psychometric characteristics